Rumor, prodigia and ideology in the Flavian period - Diego M. ESCÁMEZ DE VERA (Studia Historica: Historia Antigua, 2016)
In the present paper we will analyze the role of rumor as a way of spreading prodigia during the Flavian period. The prodigia,perfectly ingrained in the system of religious legitimization of the ruler in roman times, are considered a direct expression of the will of the deity,which shows its support or rejection. The apparent knowledge of classics about how the rumor operates, and the continuous link established between it and the appearance and spreading of prodigia, lead us to propose a political use of both phenomena during the Empire. Through the comparison between classics and modern psychology of rumor, we will analyze to what extend the link between prodigia and rumor is relevant to understand the roman prodigia.